(untitled) (LACCEI, 2024)
Abstract-The environmental impacts generated by the tourism activity is a very worrying reality, has caused the development of sustainable objectives worldwide, through which the hotel sector has transformed its traditional strategies to meet these objectives. Therefore, the present research aimed to compare some of the green strategies found at the international level, from 2018 to 2022. From the analysis of the document issued by Hernandez et al., (2020) "Resources and capabilities in the adoption of a green marketing strategy: evidence in tourism hotels" the strategies were identified based on the structure of the 4Ps of marketing with a green approach, at the same time strategic examples of international hotels that put sustainability into practice were taken. An analysis was also made pointing out their strengths and weaknesses, finding that some of these apply much more complex technologies that make implementation difficult in some sectors and to hotels of lower classification. Likewise, the consequences of environmental pollution in air, water and soil that also affect human health were developed, and a proposal of strategies was elaborated taking as an example the strategies found at international level, especially for SMEs. It is concluded that foreign countries have been more committed to sustainable implementation since much earlier in the hotel industry, in recent years there has been a greater commitment to change, so it is necessary to continue contributing to the green strategic measures that minimize environmental impacts.